Tinjauan Terhadap Metode Pembelajaran Bahasa Arab: Metode Nahwu Terjemah, Metode Langsung, Metode Audiolingual Dan Metode Gabungan - Alvia Putri Prima Sari (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2018)
Arabic language plays a big role in the lives of Muslims in Indonesia. Teaching this precious language, especially for non-native speakers, requires the appropriate method to help teachers in achieving the desired learning goals and to assist the learner in understanding the material as well as eliminate the flatness situation in the classroom. There are a variety of methods to apply, such as: translation method, direct method, audio-lingual method and combined method, where each of these methods has its advantages and disadvantages as well as positive and negative characteristics. Before choosing a method, each teacher should understand the meaning of ‘approaches’, ‘methods’, and ‘uslub’, in order to facilitate them in an effort to find the right methods.